BUSUR MAGMATIK GRANIT TANTAN-NAGAN SEBAGAI POTENSI REE DI JAMBI - Said, Yulia Morsa; Bagus, Bagus Adhitya; Siregar, Anggi Delliana; Utama, Hari Wiki; Ritonga, Magdalena; Kurniantoro, Eko (Institut Teknologi Nasional Yogyakarta, 2019)
REE (Rare Earth Element) or Rare Earth Elements are minerals that contain one or more elements which contained in a group of 17 chemical elements, this group consists of the chemical group lanthanide (lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium) are added with scandium and yttrium. In the era of Industry 4.0 or modern industry REE (Rare Earth Element) is a very strategic commodity, the use of rare earth elements is needed in various fields ranging from the electronics industry, telecommunications, modern transportation industry and many more. The REE (Rare Earth Element) density in Jambi-Sumatra occurred since the Early Mesozoic period, which was preceded by the formation of the Tantan Granite Formation to the Cenozoic period in the form of the Nagan Granite Formation.. The research location is in the Manau River, Merangin Regency which is part of the Sunda magmatic arc consists of intrusions granodiorite plutonic rock with xenolites in the form of andesites, micro diorites and diorites in the Tantan Formation, and in Nagan Formation consistsof intrusion of granite, granodiorite and Adamelit rocks. It’s happen because the forming process of REE (Rare Earth Element) mineral deposits is strongly associated with the cooling of plutonic igneous rocks. The purpose of this study are to determine the geological condition of the study area and its relationship to the REE (Rare Earth Element) and to find the potential of REE contained in the Tantan Formation and Nagan Formation in Merangin District, Jambi Province.